A prospective 1-year study of postural tachycardia and the relationship to non-postural versus orthostatic symptoms. (3rd June 2015) - Baker, J; Palamarchuk, IS; Kimpinski, K
Abstract : Background: Postural tachycardia syndrome (POTS) is defined as heart rate (HR) increments ≥30 bpm on head-up tilt (HUT) associate with orthostatic symptoms (lightheadedness, dizziness, palpitations, etc.). A large proportion of asymptomatic young adults naturally express excessive HR increments on HUT, which has raised questions regarding whether revision to the diagnostic criteria for POTS in younger patient populations is needed. In addition, poor adaptation to environmental stressors may contribute to the disability experienced by POTS patients. Objectives: 1) determine whether asymptomatic patients were predisposed to developing constitutional symptoms that could result in the full syndrome of POTS, and 2) determine whether these symptoms correlated to postural HR or orthostatic symptoms. Methods: HR response to HUT and orthostatic and constitutional symptoms in 30 asymptomatic POTS patients were evaluated after 1 year. Results: HR increment at follow-up demonstrated no correlation with general fatigue (r = 0.006), body vigilance (r = 0.195), physical (r = -0.087) and mental (r = -0.137) health, or orthostatic scores (r = 0.04). Orthostatic scores significantly correlated with general fatigue (r = 0.374) and body vigilance (r = 0.392) (p<0.05). Conclusion: These data support that the majority of young individuals express benign orthostatic tachycardia and further argue for re-evaluation of the HR criteria for diagnosing POTS in younger populations.